Tuberculosis is a Common Cause of Post-Liver Transplant Ascites: An Observational Study - R., Sowmya T.; Kulkarni, Anand V.; Sharma, Mithun; Reddy, Raghuram; Menon, Balachandran P.; Reddy, Nageshwar; Rao, Padaki Nagaraja (Journal of Gastrointestinal Infections, 2022)
Background Ascites is expected to resolve within 2 to 4 weeks following orthotopic liver transplantation. New-onset ascites after transplant is associated increased morbidity and affects quality of life. The risk of opportunistic infections is high in transplant recipients due to immunosuppressive drugs.Objective The objective was to assess the incidence of new-onset ascites in the transplant recipients and describe the cause and course of the same.Methods We retrospectively collected data of all the patients who underwent liver transplantation at our center from April 1, 2020 to April 1, 2021. The details of patients developing ascites post-liver transplantation were retrieved. The patients were followed up for 1 year after transplant.Results A total of 95 patients underwent living donor liver transplantation at our center. The incidence of new-onset ascites was 8.42% (8/95). Six out eight patients were diagnosed with tubercular ascites of whom one had disseminated tuberculosis. None of the patients had concomitant pulmonary tuberculosis. Ascites secondary to hypoalbuminemia was reported in two patients. Immunoglobulin A nephropathy and tacrolimus therapy were the underlying causes of proteinuria.Conclusion Tuberculosis was the leading cause of ascites in post-transplant period in our study. Tuberculosis should be considered as a differential diagnosis while evaluating these patients especially in the Asia-Pacific region. Being a potentially curable cause, timely diagnosis and treatment significantly improves graft survival.
Keywords: liver transplantation; mycobacterium tuberculosis (MTB); IgA nephropathy; post-transplant tuberculosis; tuberculous peritonitis; peritoneal tuberculosis